2019
DOI: 10.1136/bmjopen-2019-029144
|View full text |Cite
|
Sign up to set email alerts
|

“Stages of change, smoking behavior and acceptability of a textmessaging intervention for tobacco cessation among cigarette, dokha and shishasmokers: A qualitative research study.”

Abstract: ObjectivesTo explore: (A) the underlying motivators and barriers to smoking cessation among young Arabic speaking smokers and (B) to examine the suitability and preferences for tobacco cessation interventions (specifically text messages) and study the possibility of enrollment methods for a randomised controlled study using text messages as an intervention for tobacco cessation.DesignQualitative research using focus group discussions and content analysis.Setting(s)Two universities, one of them is the first and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Other studies have shown that smokers favoured smartphone-enabled social media applications such as WhatsApp and Snapchat for smoking cessation efforts. 22 , 27 The suggestions of counsellors to incorporate information through social media is feasible. In India, there is an increasing availability and decreasing cost of the internet and smartphones.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that smokers favoured smartphone-enabled social media applications such as WhatsApp and Snapchat for smoking cessation efforts. 22 , 27 The suggestions of counsellors to incorporate information through social media is feasible. In India, there is an increasing availability and decreasing cost of the internet and smartphones.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that tailored text messaging could have great potential in helping smokers quit yet, acceptability of interventions using text messaging is not known in certain populations. 36 Truck driving is a primarily blue-collar industry, 5 and addressing cigarette smoking among blue-collar workers can be challenging for several reasons including a lack of smoking bans at worksites. For example, research has found that bluecollar worksites are less likely to have smoking bans than white-collar worksites yet, smoking bans at worksites has been found to influence reduced smoking.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that tailored text messaging could have great potential in helping smokers quit yet, acceptability of interventions using text messaging is not known in certain populations. 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After taking the action, the individuals should maintain this new behavior over time. 11 Based on this example, we can argue that changing behavior is a long process, and single intervention is not sufficient to achieve the behavior change.…”
Section: Theory Of Behavior Changementioning
confidence: 99%